Quality of Life Research in Saskatoon, Canada: Fifteen years of co-creating knowledge and action in the community (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2016)
The quality of life research program was envisioned as an undertaking to achieve deep and balanced (quantitative and qualitative) understanding of the community and to use this knowledge to guide change to improve quality of life for all in Saskatoon. To accomplish this, the program set its sights on undertaking participatory action research, soliciting meaningful and frequent input from the community at large not only on research questions and methods but also on the implication of results, and disseminating knowledge widely. The program was intended to be longterm and longitudinal (repeated cohorts) to allow ongoing evaluation and monitoring of community outcomes, and continued guidance for ways of improving quality of life.